TRAINING PENDEKATAN TAFSIR TRANSFORMATIF: DISKURSUS DOUBLE TAXS PERSPEKTIF MASDAR FARID MAS'UDI DI HIMPUNAN MAHASISWA YAYASAN AL-KAHFI - Ikhlas Budiman; Besse Herlina Taha; Abdur Rokhim Hasan; Nur Arfiyah Febriani; Mohamad Zaenal Arifin; Nurcholik Achmad (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2025)
The issue of meditation continues to grow in the world because meditation is a solution for solving problems in the modern era to calm the mind and soul. Historically meditation originated outside Islam, but in its development it has become the property of all religions. This means that the principles of meditation are still recognized, but its implementation is in accordance with the Shari'a that has been regulated by the Qur'an and the Sunnah of the Prophet. So in Islam there is a sign of harmony between the types of meditation and the worship carried out by Muslims such as prayer, meditation, dhikr, thanksgiving and itikaf. There are findings that meditation in Islam is different from meditation from other beliefs such as Christian, Buddhist and Javanese meditation. Then integrate it with Tafsȋr Ibnu Katsȋr as a classical mufassir and Hamka who is present as a reforming mufassir who contextualizes tafakur in an Indonesian context